Revelations : art of the Apocalypse - Grubb, Nancy (New York ; London : Abbeville Press, 1997)
For nearly two thousand years, artists have been envisioning the end of the world as described in the biblical Book of Revelation. Their wonderfully strange creations - from Luca Signorelli's heroic angel warriors to William Blake's nightmarish beasts, and from Giotto's flower-strewn heaven to Howard Finster's blood red hell - fill Revelations: Art of the Apocalypse. The introduction to Revelations: Art of the Apocalypse provides an enlightening overview of the ancient sources, multilayered meanings, and mystifying symbolism of Revelation. Individual chapters are devoted to specific aspects of the diverse imagery, ranging from the apocalyptic angels and the four horsemen to Antichrist and the beasts, from the resurrection and Last Judgment to "the new heaven and the new earth." Biblical quotes are interwoven with illuminated manuscripts, frescoes, oil paintings, tapestries, stained glass, and sculpture. Some of Western culture's most compelling painters are represented, including Fra Angelico, Hieronymus Bosch, Michelangelo, Peter Paul Rubens, and Joseph Mallord William Turner, as well as medieval artisans and twentieth-century Outsider artists.
Introduction : visions of the world to come -- Angels of the Apocalypse -- The four horsemen and the seven seals -- The beasts, Antichrist, and the women -- Judgment Day -- The devil and the damned -- A new heaven and a new earth.
Includes bibliographical references (page 142) and index.
Keywords: Bible. -- Illustrations; Apocalyptic art